(3GdYbdGfjhf (B:s (3CaQGN GdeYJRdI GdYUQjhf (B/s - (3GdCKQj, Ydj Hf MSf Hf Ydj Hf YHO GdMejOs 1960-2020 ((3GdeOjfI GdefhQI (B- (3GdSYhOjI (B:s (3ecJHI GdZQHGA GdCKQjI ,s, 1993)
(3jJfGhd cJGH (B((3GdYbdGfjhf CaQGN GdeYJRdI GdYUQjhf(B) (3hGdPj bGe HJCdjag Ydj Hf MSf Hf Ydj Hf YHO GdMejO GdWHj GdCKQj, ehVhY (B((3GdYbdGfjhf(B) (3gPG GdcJGH eajOG ddWdGH hGdHGMKjf hGdegJejf HGdacQ GdESdGej hGdYbdGfj hGdeYJRdI, ceG jYO eUOQG bjeG ddeYQaI hGdage GdYejb dJGQjN GdadSaI GdESdGejI hJWhQgG YHQ GdJGQjN(B. (3agh jJMOK HTcd hGSY hjYQV Cge GdfbGW hGdCacGQ GdeJYdbI HgPG GdJjGQ GdacQj, HOGjJG HJYQja GdYbd hefRdJg aj GdESdGe, hGdYbdGfjI bOjeG hMOjKG, hehba GdYbdGfjhf ef GdSfI(B. (3ceG jbOe GdcJGH JMdjdG ehVhYjG ddJjGQ GdeYJRdj GdYUQj hehGbag(B. s
Keywords: (3GdaQb GdESdGejIs -- (3GdeYJRdIs